How boron doping shapes the optoelectronic properties of canonical and phenylene-containing oligoacenes: a combined experimental and theoretical investigation - Kirschner, Sven; Mewes, Jan-Michael; Dreuw, Andreas (Chemistry - a European journal, 2017)
Optimized syntheses of 6,13-dimesityl-6,13-dihydro-6,13-diborapentacene (DBP) and a related compound (DBI) featuring two biphenylene-2,3-diyl units in place of naphthalene-2,3-diyl moieties are reported. Striking differences between the optoelectronic properties of DBP and DBI have been experimentally observed, and explained by quantum chemical calculations.